Evaluation of Bread Wheat Genotypes for Stripe Rust Resistance - Magar, P. B.; Baidya, S.; Thapa, D. B.; Subedi, M.; Basnet, R.; Pant, K. R. (Journal of Agriculture and Environment, 2021)
Stripe rust disease is a major problem for wheat production in the hills of Nepal. To find resistance sources against this disease, 444 and 457 wheat genotypes received from National Wheat Research Program, Bhairahawa in 2018 and 2019 respectively were evaluated at Khumaltar under inoculated high disease pressure field condition. Disease was evaluated at both seedling and adult stages. In 2018, 315 genotypes showed resistance at seedling stage while 89 genotypes were having adult plant resistance (APR). Also, 71 entries showed immune response and 191 were resistant at both stages. Similarly in 2019, 233 genotypes were resistant at seedling stage and 201 were showing APR. Likewise, 35 entries were immune and 208 were resistant at both stages. Wheat genotypes with APR gene(s) can be utilized for developing durable stripe rust resistant varieties in the future. In addition, the genotypes having both stages resistant could also be used as sources of major and minor gene(s) for stripe rust resistance genotypes development in future breeding purposes.